Effect of Leadership Styles on Employee Motivation and Job Satisfaction in Multinational Corporations in Vietnam - Nguyen, Binh (International Journal of Strategic Management, 2023)
Purpose: The aim of the study was to assess the effect of leadership styles on employee motivation and job satisfaction in multinational corporations in Vietnam Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: The results showed that transformational leadership was the most preferred and effective style for enhancing employee motivation and job satisfaction, followed by democratic leadership. Autocratic and laissez-faire leadership styles were found to have negative effects on employee outcomes. The study also revealed that cultural differences, organizational climate, and individual factors influenced the perception and preference of leadership styles among employees and managers. The study concluded that MNCs in Vietnam should adopt a flexible and adaptive leadership approach that matches the needs and expectations of their diverse workforce. Unique Contribution to Theory, Practice and Policy: Transformational Leadership Theory, Expectancy Theory and Social Exchange Theory may be used to anchor future studies on the effect of leadership styles on employee motivation and job satisfaction in multinational corporations in Vietnam. Multinational corporations operating in Vietnam should benefit from the research findings to tailor their leadership training programs. Policymakers can make informed decisions about regulations that promote employee well-being, productivity, and retention in multinational corporations.